2008
DOI: 10.1063/1.2948933
|View full text |Cite
|
Sign up to set email alerts
|

Residual and fracture strains of Bi2223 filaments and their relation to critical current under applied bending and tensile strains in Bi2223∕Ag∕Ag alloy composite superconductor

Abstract: Mechanical and electromagnetic stresses are exerted on Bi2223∕Ag∕Ag alloy superconducting composite tapes during fabrication∕winding and operation, which cause reduction in critical current when the Bi2223 filaments are damaged. In the damage process, the thermally induced residual strain and fracture strain of the Bi2223 filaments play a dominant role. The aim of the present work was to propose a comprehensive method for estimation of these strain values and a quantitative description method of the relation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 28 publications
0
53
0
Order By: Relevance
“…3 shows the measured stressstrain curves. Concerning the influence of the fracture of filaments on the stress-strain curve, the following features have been revealed [10,11]: (1) The stress carrying capacity of a composite is reduced when filaments are fractured. Accordingly, the slope of the stress-strain curve is reduced in comparison with the extrapolation of the slope in a region where no filaments are fractured.…”
Section: Estimation Of Fracture Strain Of Bscco Filaments In the Nonlmentioning
confidence: 99%
See 1 more Smart Citation
“…3 shows the measured stressstrain curves. Concerning the influence of the fracture of filaments on the stress-strain curve, the following features have been revealed [10,11]: (1) The stress carrying capacity of a composite is reduced when filaments are fractured. Accordingly, the slope of the stress-strain curve is reduced in comparison with the extrapolation of the slope in a region where no filaments are fractured.…”
Section: Estimation Of Fracture Strain Of Bscco Filaments In the Nonlmentioning
confidence: 99%
“…It has been shown that the Weibull distribution is a useful tool for description of a critical current distribution [10,[13][14][15]. In this section, first, whether the critical current distribution of the nonlaminated and laminated samples is described by this function or not was examined, and, based on the result, influences of lamination on the distribution of the critical current were studied.…”
Section: Distribution Of Critical Current In the Non-laminated And Lamentioning
confidence: 99%
“…Because the " r is negative (compressive) in the Bi2223 composite tape, as has been demonstrated by X ray diffraction analysis, 7,8) the actual fracture strain of the filaments in the composite tape is by À" r higher than the intrinsic fracture strain " f of the filaments alone. 2,4,[6][7][8]11,14) The " f À " r value is different from location to location within a specimen as well as from specimen to specimen. In the preceding works, 11,12) the heterogeneous damage behavior was formulated by the distributed " f À " r values and was correlated to the distribution of critical current values.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Heterogeneous damage occurs, and the damage evolution behavior differs from specimen to specimen and from location to location within a specimen. [9][10][11][12][13][14] Accordingly, when a number of specimens are tested, the critical current differs from specimen to specimen.…”
Section: Introductionmentioning
confidence: 99%
“…In order to describe the critical-current degradation of Bi2223/Ag composite tapes from bending strain, some empirical formulae based on experimental observations were presented [10][11][12][13][14][15][16][17][18]. Haken et al [10] first investigated the critical-current I c , as a function of axial strain in Bi-2212/Ag superconducting composite wires, and a descriptive model based on experimental data was proposed and further utilized to analyze the bending deformation influence on the critical-current in pre-strained wires within different tension/compression strain regimes.…”
Section: Introductionmentioning
confidence: 99%